Relationship skills in social work - Hennessey, R. A. S. (Roger A. S.) (Los Angeles, Calif. : SAGE, 2011)
Human relationships lie at the heart of social work practice, and an understanding of their importance is a crucial aspect of training. This text considers the place of relationships in current practice and explores the ways in which social workers can use relationship skills to achieve the best possible outcomes for their clients.
1. Introduction to relationships in social work -- 2. The centrality of relationships in social work -- 3. The theoretical bases of relationship based social work -- 4. Knowing and using oneself in relationship based social work -- 5. Knowing the other person in relationship based social work -- 6. Sustaining oneself in relationship based social work -- 7. The ethics of relationship based social work -- 8. Drawing themes together: theory and the use of personal experience.
Includes bibliographical references and index.
Keywords: Social service; Social workers -- Professional relationships